Blood and seminal plasma concentrations of selenium, zinc and testosterone and their relationship to sperm quality and testicular biometry in domestic cats - Villaverde, Ana Izabel S. B. [UNESP]; Fioratti, Eduardo G. [UNESP]; Ramos, Renata S. [UNESP]; Neves, Renato C. F. [UNESP]; Ferreira, João Carlos Pinheiro [UNESP]; Cardoso, Guilherme S. [UNESP]; Padilha, Pedro de Magalhães [UNESP]; Lopes, Maria Denise [UNESP] (Elsevier B.V., 2014)
The aim of this study was to assess seminal plasma (SP) and serum concentrations of zinc (Zn), selenium (Se) and testosterone (T) in domestic cats and determine whether these are related to sperm quality and testicular biometry. Six tomcats were collected using an artificial vagina and sperm analysis included motility by CASA, morphology, plasma membrane integrity, and sperm count. Serum and SP were submitted to total T concentration determination using a solid-phase radioimmunoassay technique while Zn and Se were measured by atomic absorption spectroscopy. Serum T concentrations were greater compared to SP concentrations, but both values were significantly correlated. Se concentrations were higher in serum, whereas SP had greater Zn values. Concentrations of Se, Zn and T were not correlated with each other either in serum or SP. Negative correlations were detected between Se concentrations in SP and total sperm head defects, and between Se concentrations in serum and VAP, VSL, SIR, and LIN. Serum concentrations of Zn were negatively correlated with total abnormal sperm and midpiece defects and positively related to progressive motility. Both serum and SP concentrations of T had no relationship with sperm quality. Concentrations of Se exhibited a negative correlation with total testicular weight, whereas T concentrations in SP and serum were correlated with total testicular volume and weight. In conclusion, both Se and Zn concentrations in serum were correlated to sperm quality variables in the domestic cat, thus, making these potential candidates for fertility markers. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Trace elements; Sperm morphology; Sperm motility; Testicular biometry